Preharvest Methyl Jasmonate Treatment Increased Glucosinolate Biosynthesis, Sulforaphane Accumulation, and Antioxidant Activity of Broccoli - Junwei Wang; Shuxiang Mao; Mantian Liang; Wenxia Zhang; Fangzhen Chen; Ke Huang; Qiuyun Wu (MDPI AG, 2022)
Broccoli is becoming increasingly popular among consumers owing to its nutritional value and rich bioactive compounds, such glucosinolates (GSLs) and hydrolysis products, which are secondary metabolites for plant defense, cancer prevention, and higher antioxidant activity for humans. In this study, 40 μmol/L methyl jasmonate (MeJA) was sprayed onto broccoli from budding until harvest. The harvested broccoli florets, stem, and leaves were used to measure the contents of GSLs, sulforaphane, total phenolics, and flavonoids, as well as myrosinase activity, antioxidant activity, and gene expression involved in GSL biosynthesis. The overall results revealed that GSL biosynthesis and sulforaphane accumulation were most likely induced by exogenous MeJA treatment by upregulating the expression of CYP83A1, SUR1, UGT74B1, and SOT18 genes. Exogenous MeJA treatment more remarkably contributed to the increased GSL biosynthesis in broccoli cultivars with low-level GSL content (Yanxiu) than that with high-level GSLs (Xianglv No.3). Moreover, MeJA treatment had a more remarkable increasing effect in broccoli florets than stem and leaves. Interestingly, total flavonoid content substantially increased in broccoli florets after MeJA treatment, but total phenolics did not. Similarly, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity, trolox-equivalent antioxidant capacity (ABTS), and ferric-reducing antioxidant power (FRAP) were higher in broccoli floret after MeJA treatment. In conclusion, MeJA mediated bioactive compound metabolism, had positive effects on GSL biosynthesis, sulforaphane, and flavonoids accumulation, and showed positive correlation on inducing higher antioxidant activities in broccoli floret. Hence, preharvest supplementation with 40 μM MeJA could be a good way to improve the nutritional value of broccoli florets.